2018
DOI: 10.1111/ajpy.12162
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and ideological correlates of negative attitudes towards asylum seekers: A meta‐analytic review

Abstract: Objective: A global increase in forced displacement has led to rapid increases in the number of people seeking asylum. Negative attitudes toward these people are pervasive and the literature attempting to understand the prevalence and impact of these attitudes is growing. This article contains a meta-analysis of the Australian quantitative research in this field. Method: We combined effect sizes from published and unpublished Australian data. The primary outcomes were effect size estimates for the correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 42 publications
2
53
0
2
Order By: Relevance
“…In a recent study, Anderson (2018) found that national identification was strongly associated with conditional prejudice, r = 0.42, p < 0.001, rather than classical prejudice, r = 0.19, p < 0.05, against asylum seekers. A recent literature review suggested that being high in national identification is related to harbouring negative attitudes toward asylum seekers (Anderson and Ferguson 2018). Similar results emerged in another study, where high levels of national identity were more strongly related to negative attitudes than personality-based attitudes, such as self-esteem, toward asylum seekers (Pedersen et al 2005).…”
Section: National Identificationsupporting
confidence: 60%
See 2 more Smart Citations
“…In a recent study, Anderson (2018) found that national identification was strongly associated with conditional prejudice, r = 0.42, p < 0.001, rather than classical prejudice, r = 0.19, p < 0.05, against asylum seekers. A recent literature review suggested that being high in national identification is related to harbouring negative attitudes toward asylum seekers (Anderson and Ferguson 2018). Similar results emerged in another study, where high levels of national identity were more strongly related to negative attitudes than personality-based attitudes, such as self-esteem, toward asylum seekers (Pedersen et al 2005).…”
Section: National Identificationsupporting
confidence: 60%
“…Furthermore, national identification was indirectly related to the outcome variable through intergroup anxiety. Anxiety about interacting with asylum seekers has been found to predict fewer positive attitudes toward them (Anderson 2018;Anderson and Ferguson 2018;Visintin et al 2017). This result can be explained by the context in which the present study measured intergroup anxiety.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The primary concern for the findings presented in this paper pertain to the composition of the sample; the data were provided by a relatively young student sample which is typically known to have more progressive social attitudes that the wider population. A recent meta‐analysis has shown that the relationship between demographic variables and negative attitudes toward asylum seekers is not moderated by student status (Anderson & Ferguson, ), thus this should be of little concern to the interpretation of these results. Regardless, these sampling factors should be considered when interpreting and generalising these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been rapid increases in the prevalence of asylum seekers; the end of 2015 reported over 65 million reported cases of displaced individuals (the highest figure in recorded history, including both world wars; Edwards, ). This vast and global increase has resulted in tumultuous social attitudes toward this group ranging from compassionate to hostile (for a recent review, see Anderson & Ferguson, ). In order to produce and evaluate prejudice‐based interventions, researchers have been establishing correlates and predictors of explicit (Hartley & Pedersen, ; Pedersen, Attwell, & Heveli, ) and implicit (Anderson, ; Anderson & Cheers, ) attitudes toward asylum seekers.…”
Section: Social Attitudes and Implicit–explicit Measurementmentioning
confidence: 99%